Strengthening Cultural Bridges Through Interfaith Approaches Toward Global Harmony (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: This paper “Strengthening Cultural Bridges Through Interfaith Approaches Toward Global Harmony” explores the evolving nature of religious boundaries in a modern, interconnected world and offers practical strategies for fostering global unity through interfaith dialogue. The paper examines how historical divisions between religious communities have been transformed by globalization, pluralism, and secularism, resulting in both opportunities and challenges for interfaith cooperation. It emphasizes the importance of understanding and respecting religious boundaries while promoting dialogue, empathy, and shared values to address global issues such as conflict, inequality, and environmental degradation. By presenting real-world case studies and actionable frameworks, this study aims to equip individuals, faith leaders, and policymakers with the tools to navigate religious diversity, reduce prejudice, and cultivate peaceful coexistence in diverse societies.Methodology: In this paper, the exploratory qualitative research method is used. The relevant information is collected using keyword-based search in Google search engine, Google Scholar search engine, and AI-driven GPTs. This information is analysed and interpreted as per the objectives of the paper.Results/Analysis: Studies indicate that for successful interfaith cooperation, there should be clear boundaries and a well-structured dialogue along with respect between communities. Technology offers religious communities the opportunity to connect, learn, and collaborate without being geographically constrained. However, fostering meaningful interfaith relationships requires the careful building of trust through face-to-face interactions and shared activities.Originality/Values: In today's world, conflicts within different religions and beliefs can lead to divisive issues. Compassion and understanding are vital components to construct bridges between communities throughout the globe.Type of the Paper: Exploratory Analysis.
Keywords: Interfaith dialogue; Religious boundaries; Global unity; Religious pluralism; Peacebuilding